Mandibular advancement appliance effects on obstructive sleep apnoea: a prospective threedimensional computed tomography study - Ghoneima Ahmed; Bodkin Cynthia; Stewart Kelton; Perlow Mark J.; Starbuck John; Kula Katherine (Sciendo, 2017)
The aim of this study was to determine the effects of an elastic mandibular advancement (EMA) appliance on upper airway dimensions, most constricted area (MCA) of the airway, and snoring in a sample of obstructive sleep apnoea (OSA) patients of varying severity.